Определение джучидских монет с городища Царино (из раскопок М.Л. Швецова в 1988-1991 гг) - Евглевский, А.В. (Степи Европы в эпоху средневековья, 2012)
The paper describes coins (1 dirkhem and 17 puls) from the Tsarino hillfort which were excavated by M.L.Shvetsov in 1988-1991 and passed to the author for determination in April, 2011. Six drawings of the puls found at the same hillfort have been analyzed, with the location of these coins being so far unknown. The monetary complex consists of 24 coins of khans as follows: Berdibek (1 dirkhem), Abdallah (8 puls), Mohammed-Bulak (11 puls), Toktamysh (?), probably, imitations (2 puls). Two more puls cannot be attributed because of very poor condition. Six puls found in the occupation layer or, more precisely, at different places of IT excavation site, are of special importance. These coins permit not only to determine the chronology of a number of constructions of the hillfort, but also to precisely indicate the times of existence of the settlement by individual periods. On the whole, the collection combined with other numismatic finds from the Tsarino hillfort accumulated by archaeologists and specialists on local history within a long period gives ground to assume that the beginning of the settlement can be dated since the 2nd half of 1350s, and the upper time limit when it was abandoned which may presumably be defined as the time of Toktamysh’s rule, namely 1395 when the settlement appears to have been demolished by Tamerlane’s troops.